2018
DOI: 10.1021/acs.jproteome.8b00129
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1-Dependent Cell Cycle Proteomics

Abstract: The HTRA1 gene encoding an evolutionary conserved protein quality-control factor can be epigenetically silenced or inactivated by mutation under pathologic conditions such as cancer. Recent evidence suggests that the loss of HTRA1 function causes multiple phenotypes, including the acceleration of cell growth, delayed onset of senescence, centrosome amplification, and polyploidy, suggesting an implication in the regulation of the cell cycle. To address this model, we performed a large-scale proteomics study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…We also showed that obesity down-regulates the expression of HTRA1 gene encoded serine protease with IGF-binding domain, which functions as important modulators of many physiological processes, including cell signaling and apoptosis, regulates the availability of IGFs by cleaving IGFBPs and has a pivotal role in both cell proliferation and differentiation (D'Angelo et al 2014;Zurawa-Janicka et al 2017;Schillinger et al 2018). Our results concerning the obesity related changes in HTRA1 expression agree with data of Tiaden et al (2016) that this enzyme, as a negative regulator of mesenchymal stem cells adipogenesis, participates in the adipose tissue remodeling under pathological conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We also showed that obesity down-regulates the expression of HTRA1 gene encoded serine protease with IGF-binding domain, which functions as important modulators of many physiological processes, including cell signaling and apoptosis, regulates the availability of IGFs by cleaving IGFBPs and has a pivotal role in both cell proliferation and differentiation (D'Angelo et al 2014;Zurawa-Janicka et al 2017;Schillinger et al 2018). Our results concerning the obesity related changes in HTRA1 expression agree with data of Tiaden et al (2016) that this enzyme, as a negative regulator of mesenchymal stem cells adipogenesis, participates in the adipose tissue remodeling under pathological conditions.…”
Section: Discussionmentioning
confidence: 88%
“…The HTRA1/PRSS11 gene encoded serine protease with IGF-binding domain, which functioning as important modulators of many physiological processes, including cell signaling and apoptosis, regulates the availability of IGFs by cleaving IGFBPs and has a pivotal role in both cell proliferation and differentiation (D'Angelo et al 2014;Zurawa-Janicka et al 2017;Schillinger et al 2018). Recently, it has been shown that lysyl oxidase regulates the epidermal growth factor receptor to facilitate its activation by EGF to drive tumor progression by suppressing TGFβ1 signaling through the secreted protease HTRA1 (Tang et al 2017).…”
mentioning
confidence: 99%
“…HeLa cells (kind gift from Prof. Dr. C. Azzalin, ETH Zurich, Switzerland) and human dermal fibroblasts (106-05N, Sigma-Aldrich, St. Louis, MI) were cultured in DMEM medium supplemented with 10% fetal bovine serum and 1% (v/v) penicillin/streptomycin in a 5% CO 2 atmosphere. THP1 monocytes (kind gift from Dr. H.-D. Beer, University of Zurich, Switzerland) and SW480 cells engineered for overproduction or down-regulation of HtrA1 17,18 (kind gift from Prof. Dr. M. Ehrmann, University Duisburg-Essen, Germany) were cultured in RPMI medium supplemented with 10% fetal bovine serum, 1% (v/v) penicillin/streptomycin plus G418 or puromycin, respectively, in a 5% CO 2 atmosphere. Transfection was performed using Lipofectamine 2000 according to the manufacturer's instructions.…”
Section: Culture and Transfection Of Cellsmentioning
confidence: 99%
“…In human cells, several reports sampled the proteome in the cell cycle with mass spectrometry, but there is little consensus among them (Dephoure et al ., 2008; Olsen et al ., 2010; Lane et al ., 2013; Ly et al ., 2014; Becher et al ., 2018; Dai et al ., 2018; Schillinger et al ., 2018). The fraction of proteins identified as periodic ranged from ∼5% (Ly et al ., 2014), to >65% (Schillinger et al ., 2018). Synchronization was mostly achieved by release from chemical arrest, but two studies also used elutriation (Ly et al ., 2014; Dai et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the only report where an experiment-matched transcriptomic dataset was generated (Ly et al ., 2014), the correlation with transcript abundance was positive (ρ=0.63, based on the Spearman rank correlation coefficient). Some of the differences among the above studies may arise from the use of different cell lines, such as: HeLa (Dephoure et al ., 2008; Olsen et al ., 2010; Lane et al ., 2013; Becher et al ., 2018); K562 (Dai et al ., 2018); SW480 (Schillinger et al ., 2018); or NB4 (Ly et al ., 2014). However, even for the same cell line (HeLa), synchronization (release from thymidine block and nocodazole arrest), and point in the cell cycle (0.5 h after nocodazole arrest), the relative change in abundance of the 3,298 proteins identified in common between the two studies (Olsen et al ., 2010; Becher et al ., 2018) was uncorrelated (ρ=0.097, based on Spearman’s rank correlation coefficient; see Materials and Methods).…”
Section: Introductionmentioning
confidence: 99%